PERBANDINGAN PERHITUNGAN RETURN PORTOFOLIO ANTARA FAMA AND FRENCH THREE FACTORS MODEL DAN CAPITAL ASSET PRICING MODEL PADA BURSA EFEK INDONESIA PERIODE 2005-2013 - Hendi Hendi (STIE Wiyatamandala, 2017)
CAPM is old theory that used to be taught in most of business school today. But empirically this model is fail to explain excess return of portfolio. The study seeks to determine the risk factors in asset pricing in the Indonesian Stock Exchange through a comparative analysis of the three factors model and the Capital Asset Pricing Model. In this research, each Daily Return are analyzed using Fama French and CAPM Model. Both model are compared its R2 result and tested using F test and T test. Our finding is the R2 result are not really different between Fama French Model and CAPM. Our result confirm that CAPM still good asset pricing model base on our sample experiment.